On superfield covariant quantization in general coordinates - Gitman, D. M.; Moshin, P. Yu; Tomazelli, J. L. [UNESP] (Springer Nature, 2005)
We propose a natural extension of the BRST-antiBRST superfield covariant scheme in general coordinates. Thus, the coordinate dependence of the basic tensor fields and scalar density of the formalism is extended from the base supermanifold to the complete set of superfield variables. © Springer-Verlag.